2013
DOI: 10.1016/s0140-6736(13)60457-2
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-135b promotes cancer progression acting as a downstream effector of oncogenic pathways in colon cancer

Abstract: SUMMARYMicroRNA deregulation is frequent in human colorectal cancers (CRCs), but little is known as to whether it represents a bystander event or actually drives tumor progression in vivo. We show that miR-135b overexpression is triggered in mice and humans by APC loss, PTEN/PI3K pathway deregulation, and SRC overexpression and promotes tumor transformation and progression. We show that miR-135b upregulation is common in sporadic and inflammatory bowel disease-associated human CRCs and correlates with tumor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 36 publications
5
64
0
Order By: Relevance
“…MiR‐149 has been identified to be correlated with the metastasis and drug resistance to 5‐FU in CRC, and miR‐139‐5p sensitized CRC cell lines to 5‐FU treatment . Additionally, inhibition of miR‐135b in CRC mouse model reduced proliferation, invasion and apoptosis, and miR‐135b suppressed the ability of PTEN in CRC . MiR‐182 functioned as a key microRNA to promote cell proliferation, metastasis, and drug resistance in cancers according to recent studies .…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐149 has been identified to be correlated with the metastasis and drug resistance to 5‐FU in CRC, and miR‐139‐5p sensitized CRC cell lines to 5‐FU treatment . Additionally, inhibition of miR‐135b in CRC mouse model reduced proliferation, invasion and apoptosis, and miR‐135b suppressed the ability of PTEN in CRC . MiR‐182 functioned as a key microRNA to promote cell proliferation, metastasis, and drug resistance in cancers according to recent studies .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported upregulation of miR‐135b amongst several other microRNAs in colorectal tumor tissues compared with normal colonic tissue, and this was associated with increased tumor invasiveness and migration . Upregulation of miR‐135b is observed in early stages of human CRC tumorigenesis, as well as in mouse models, in tumors originating from chronically inflamed colon or caused by mutations of the adenomatous polyposis coli (APC) gene . Elevated levels of miR‐135b in colorectal tumors have been associated with several pathways, such as the Wnt pathway and the PI3K/PTEN pathway (phosphoinositide 3‐kinase/phosphatase and tensin homolog) .…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of miR‐135b is observed in early stages of human CRC tumorigenesis, as well as in mouse models, in tumors originating from chronically inflamed colon or caused by mutations of the adenomatous polyposis coli (APC) gene . Elevated levels of miR‐135b in colorectal tumors have been associated with several pathways, such as the Wnt pathway and the PI3K/PTEN pathway (phosphoinositide 3‐kinase/phosphatase and tensin homolog) . miR‐135b suppressed expression of APC, transforming growth factor β (TGFβ) and TGFβ receptor II, and of death‐associated protein kinase 1, indicating its important role during malignant transformation of colonic epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, miRNA-135b upregulation is common in sporadic and inflammatory bowel disease-associated human colorectal cancer (CRC), which correlates with tumor stage and poor clinical outcome [9]. For instance, miRNA-135b upregulation is common in sporadic and inflammatory bowel disease-associated human colorectal cancer (CRC), which correlates with tumor stage and poor clinical outcome [9].…”
mentioning
confidence: 99%